Synthesis and characterization of ZnO-based/derived nanoparticles as promising photocatalysts - Fatima, Hira (Curtin University, 2022)
Biocompatibility and the ability to create tumor-killing reactive oxygen species have drawn increasing attention to zinc oxide (ZnO) based/derived nanoparticles for photodynamic treatment. There are several variables that may affect the performance of ZnO-based NPs in PDT that can be manipulated by doping and compositing. Among these variables are the charge separation, the absorption potential, and the bandgap engineering. In this thesis, we reviewed designed and developed improved photodynamic performance ZnO based/derived nanoparticles.